Orexin, Sleep, Sympathetic Neural Activity, and Cardiovascular Function. Issue 12 (23rd September 2022) - Bigalke, Jeremy A.; Shan, Zhiying; Carter, Jason R.
Abstract : Inadequate sleep duration and quality are associated with reduced cardiovascular health and increased mortality. Experimental evidence points to the sympathetic nervous system as a key mediator in the observed relationship between poor sleep and cardiovascular dysfunction. However, brain mechanisms underpinning the impaired sympathetic function associated with poor sleep remain unclear. Recent evidence suggests the central orexin system, particularly orexins A and B and their receptors, have a key regulatory role for sleep in animal and human models. While orexin system activity has been observed to significantly impact sympathetic regulation in animals, the extension of these findings to humans has been difficult due to an inability to directly assess orexin system activity in humans. However, direct measures of sympathetic activity in populations with narcolepsy and chronic insomnia, 2 sleep disorders associated with deficient and excessive orexin neural activity, have allowed indirect assessment of the relationships between orexin, sleep, and sympathetic regulation. Further, the recent pharmaceutical development of dual orexin receptor antagonists for use in clinical insomnia populations offers an unprecedented opportunity to examine the mechanistic role of orexin in sleep and cardiovascular health in humans. The current review assesses the role of orexin in both sleep and sympathetic regulation from a translational perspective, spanning animal and human studies. The review concludes with future research directions necessary to fully elucidate the mechanistic role for orexin in sleep and sympathetic regulation in humans.